2017
DOI: 10.1155/2017/7569354
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Zn (II) by TDDA-Polypropylene Supported Liquid Membranes and Recovery from Waste Discharge Liquor of Galvanizing Plant of Zn (II)

Abstract: The facilitated passage of Zn (II) across flat sheet supported liquid membrane saturated with TDDA (tri-n-dodecylamine) in xylene membrane phase has been investigated. The effect of acid and metal ion concentration in the feed solution, the carrier concentration in membrane phase, stripping agent concentration in stripping phase, and coions on the extraction of Zn (II) was investigated. The stoichiometry of the extracted species, that is, complex, was investigated on slope analysis method and it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The steric effect of the substituent at position 2 or 4 decreases the stability constants of octahedral complexes of all the metals studied, although it does not hinder the formation of tetrahedral species [29,30,53,55,58,59,60,61,62]. The formation of tetrahedral complexes with 1-alkylimidazoles has been proven for the Zn(II) and Cd(II) ions [42,56,59,71]. The Zn(II) ions were transported across PIMs most effectively.…”
Section: Resultsmentioning
confidence: 99%
“…The steric effect of the substituent at position 2 or 4 decreases the stability constants of octahedral complexes of all the metals studied, although it does not hinder the formation of tetrahedral species [29,30,53,55,58,59,60,61,62]. The formation of tetrahedral complexes with 1-alkylimidazoles has been proven for the Zn(II) and Cd(II) ions [42,56,59,71]. The Zn(II) ions were transported across PIMs most effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Extending the exposure time between the metal ions and the hybrid membrane in a cell-type reactor can correspondingly increase the removal efficiency due to the greater chances of complex formation and its transport through the membrane from feed to strip phase. 53 Thus, the effect of reaction time on the Pb 2+ ion removal performance by the PVAc/rGO/Fe 2 O 3 membrane was studied under the optimal process parameters and the findings are shown in Fig. 10(a and b).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of various parameters such as feed concentration, carrier concentration, feed phase, and receptor pH on the separation factor and flux of Cd (II) and Ni (II) ions was studied, which concluded that the percentage of cadmium separation is much higher than a nickel 34 . Rehman et al 35 investigated the transfer of zinc (II) through the SLM flat membrane with the carrier TDDA (tri-n-dodecylamine). The stoichiometry of the extracted species, i.e., complex, was investigated using slope analysis, and it was found that complex (LH) 2 ·Zn(CL) 2 is responsible for Zn (II) transmission.…”
Section: Introductionmentioning
confidence: 99%